Kreativitas Dan Kepercayaan Diri Siswa Melalui Kegiatan Drama di SMP Muhammadiyah Terpadu - Loliek Kania Atmaja; Jelita Zakaria; Yanti Paulina (SAFARI :Jurnal Pengabdian Masyarakat Indonesia, 2024)
Aims to examine the impact of drama activities at school on increasing students' creativity and self-confidence. Drama is an art form that combines various elements such as acting, expression and social interaction, which can provide a holistic learning experience for students. We provide motivation in the form of student creativity and self-confidence and analyze student participation in drama activities held at Muhammadiyah Integrated Middle School. The results showed that drama activities significantly increased students' creativity. They are better able to express new ideas, improvise, and develop stories and characters better. Additionally, participation in drama also shows a marked increase in students' self-confidence. Students become more confident in public speaking, show courage in trying new things, and participate more actively in class discussions. Drama activities also create an inclusive and collaborative learning environment, where students feel safe to express themselves without fear of judgment. This not only helps in the development of individual skills but also strengthens the sense of togetherness and teamwork among students. Thus, implementing drama activities in schools can be an effective strategy for developing students' creativity and self-confidence. The recommendation from this research is to include drama activities more intensively and structured in the school curriculum as part of efforts to improve the quality of education.